Determinan Tax Avoidance pada Perusahaan Pertambangan yang Dimoderasi oleh Insider Ownership - Ilham Tri Oktavian Ilham; Hasan Mukhibad Hasan (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to analyze the effect of transfer pricing, fixed asset intensity, and political connections on tax avoidance. This study also raises insider ownership as a moderating variable. The presence of managerial ownership provides a dual function for managers as those who own and run the company. Managers will try to take the best policy in meeting various elements of interest, including in the field of taxation. The population in this study are multinational companies in the mining sector which are listed on the Indonesia Stock Exchange (IDX) during 2015-2020. The sample was selected using purposive sampling method and obtained as many as 168 units of analysis. Data analysis in this study used moderated regression analysis (MRA). Based on the estimation of model selection, the Random Effect Model (REM) was chosen to be the right model to test the hypothesis in this study. The results show that transfer pricing and asset intensity have a significant positive effect on tax avoidance. Meanwhile, political connections have no effect on tax avoidance. Managerial ownership is able to moderate the effect of the transfer pricing variable and fixed asset intensity on tax avoidance, however, it is not able to moderate the political connection variable. Based on this research, The company is expected to be more transparent in disclosing transactions between related parties while still paying attention to fairness values. The weakness in this study is the low proportion of company share ownership by the government so that it has not been able to influence company policy making.